POLA PENGAWASAN BAITUL MAAL WAT TAMWIL (BMT) YANG BERBADAN HUKUM KOPERASI - Beny Nurhadi (Universitas Nasional, 2018)
ABSTRACTThe emergence of sharia micro finance It aims to provide a better model in handling the issue of high interest rates and others in Islam. But technically operational is still faced with many problems need to be solved. One of them concerns the ability of Islamic legal analysis of some inadequate BMT managers, In fact, not infrequently financing officers finally mistakenly apply the actual contract. The problems in this article are two things: the functions and activities of Baitul Maal wat-Tamwil (BMT) and the pattern and mechanism of supervision on Baitul Maal wat-Tamwil (BMT) incorporated as cooperative law. The results in this article found that the functions and activities in operationalizing BMTs have been described in detail. But the pattern and mechanism of supervision BMT cooperative law is still overlapping between institutions, so that many customers are harmed.Keywords: System Supervision, Baitul Maal Wat Tamwil, Cooperative